DINAMIKA PEMAKAIAN KONTRASEPSI MODERN DI INDONESIA (ANALISIS DATA SUSENAS 2015) - Mario Ekoriano; Firma Novita (Jurnal Kependudukan Indonesia, 2018)
Data on contraceptive methods use are needed to evaluate the family planning program and contraceptive needs in the future. Therefore, it is important to understand the changing of contraceptive methods’ usage and influential factors to choose a certain contraceptive method. This study aims to find out the displacement dynamics of modern contraceptive use in Indonesia, both short term and long term methods. The study analyzed data from the National Socio-economic Survey (Susenas) in 2015 by using descriptive and inferential statistical techniques. The results of the study show a shifting on contraceptive use that was previously dominated by the short-term methods to the long terms ones, mostly by couples of childbearing age with a smaller number of children. This study also found a correlation between the choice of contraceptive method and the number of children ever born to couples of childbearing age. The changes of couples of childbearing age’s mindset on the desirable number of children are likely to be considered when deciding to shift to long-term contraceptive methods, such as tubectomy, vasectomy, IUD, and implant.